-2(7x+1)=14-6x

Simple and best practice solution for -2(7x+1)=14-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(7x+1)=14-6x equation:


Simplifying
-2(7x + 1) = 14 + -6x

Reorder the terms:
-2(1 + 7x) = 14 + -6x
(1 * -2 + 7x * -2) = 14 + -6x
(-2 + -14x) = 14 + -6x

Solving
-2 + -14x = 14 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-2 + -14x + 6x = 14 + -6x + 6x

Combine like terms: -14x + 6x = -8x
-2 + -8x = 14 + -6x + 6x

Combine like terms: -6x + 6x = 0
-2 + -8x = 14 + 0
-2 + -8x = 14

Add '2' to each side of the equation.
-2 + 2 + -8x = 14 + 2

Combine like terms: -2 + 2 = 0
0 + -8x = 14 + 2
-8x = 14 + 2

Combine like terms: 14 + 2 = 16
-8x = 16

Divide each side by '-8'.
x = -2

Simplifying
x = -2

See similar equations:

| 200=xl | | x=35313(35313*0.16) | | 6z+7=5z+6 | | 400/460 | | m-(-18)=7 | | -5x-4-5x=-24 | | 7-3y+6=-7 | | 9=5+2g | | -4(6n-4)-7= | | ax^2-bx^2=0 | | 16+c=-5 | | 1+4a-a= | | 15y+3x=61 | | 0=-16t^2+24t+40 | | 4+2q=8 | | 5n+3=4-6(6-5n) | | p+(-9)=8 | | 10=3y+1 | | -14-8k=2k+8k | | 3x=x^2+9 | | 50=x(x*0.16) | | -12+5m+10=2m-10-m | | (15/28)/35 | | t/7=-9/1 | | 8r-5q=3forq | | -d+7= | | 13x+1+12x+9= | | t/t=-9/1 | | 10x-4-6x=-84 | | 9x-81=7 | | .3+.6=.06 | | 4/24 |

Equations solver categories